Documenting South African Exile in the Polish People's Republic in the 1980s: Patrick Mabinda, Beverley Marcus, and the Lodz Film School - Macqueen, Ian; Kochajkiewicz, Adam (South African Historical Journal, 2024)
This article explores the documenting of activists' experiences in the Polska Rzeczpospolita Ludowa (Polish People's Republic, PRL) in the 1980s. It discusses the exile of Patrick Mabinda from South Africa, via Tanzania, in the PRL. Mabinda was arrested on terrorism charges in January 1977, but, after a daring escape from John Vorster Square in April 1977, he succeeded in fleeing the country and gaining a visa to Poland, facilitated by the African National Congress in Dar es Salaam. Arriving there in November 1977, he was one of a handful of South African refugees who met Beverley Joan Marcus, a South African student studying as a junior film director at the Szkoła Filmowa w Łodzi (Lodz Film School). The declassified records of the Communist Secret Police apparatus provide an (albeit limited) perspective into the level of operational interest into African National Congress associates in Poland. The close examination of two individual exile experiences of South Africans in the PRL, and their documentation through film, provides an opportunity to develop a textured analysis of the diversity of exile experiences, revealing tensions that speak to the awkward position the PRL took towards the South African liberation struggle.